The Influence Of Competence, Independence, Obedience Pressure, And Internal Control System On The Quality Of Internal Auditor Examination Results - Fakhri Ramadhan; Rini Indriani; Fachruzzaman Fachruzzaman (UNIVED Press, 2024)
This study aims to test and find empirical evidence of the effect of Competence, Independence, Obedience Pressure, and Internal Control Systems on the quality of internal auditor examination results. The population in this study were all civil servants (PNS) in the Inspectorate of Bengkulu Province, totaling 130 people. Sampling in this study uses non-probability sampling through purposive sampling, where all examiners who occupy the Auditor Functional Position (JFA) and P2UPD Functional Position at the Inspectorate of Bengkulu Province are used as a sample of 96 people. The data analysis model used in this research is multiple linear regression analysis using IBM SPSS version 25 software. The findings reveal that competence, independence, and the internal control system positively influence examination quality, while obedience pressure has a negative impact. The implication of this research is that it provides an opportunity for the inspectorate of the province of Bengkulu to pay more attention to factors that can improve the quality of examination results such as increasing auditor competence, strengthening auditor independence, how to overcome obedience pressure and strengthen and ensure an effective internal control system.